Pengaruh Kecepatan Pengadukan pada Biosorpsi Direct Blue 86 oleh Kulit Kelengkeng Termodifikasi - Anastasya Tri Yolanda; Desy Kurniawati (Lembaga Yasin AlSys, 2026)
Direct Blue 86 (DB-86) is an anionic azo dye that is widely used in the textile industry and has relatively persistent properties in aquatic environments, making low-cost adsorbents necessary for the treatment of colored liquid waste. This study aims to evaluate the effect of stirring speed on the biosorption of DB-86 using longan peel modified with duck egg white in batch mode. The biosorbent was prepared from acid-activated longan peel and duck egg white with a KL:PTI mass ratio of 1:1. Biosorption experiments were conducted using 0.2 g of biosorbent and 25 mL of 450 mg/L DB-86 solution at pH 2, a particle size of 63 µm, and a contact time of 30 minutes. Variations in stirring speed were set at 100, 150, 200, 250, 300, and 350 rpm. The dye concentration after biosorption was measured using a UV-Vis spectrophotometer at a wavelength of 627 nm and converted based on the standard curve equation. The results showed that the adsorption capacity increased from 46.734 mg/g at 100 rpm to a maximum of 51.894 mg/g at 200 rpm, with the highest removal efficiency of 95.25%. However, increasing the stirring speed to 250–350 rpm gradually reduced biosorption performance. The optimum condition at 200 rpm indicates that adequate stirring can improve solution homogeneity and external mass transfer, whereas excessive stirring may disrupt the interaction between the dye and the biosorbent. These findings emphasize the importance of optimizing stirring speed in the biosorption process and demonstrate the potential of longan peel modified with duck egg white as a low-cost biosorbent for removing anionic dyes from liquid waste.